Immunohistochemical Expression of P63 and P40 in Squamous Cell Carcinoma of Head and Neck - Zahid, Aima; Akhtar, Raana; Hameed, Samreen; Mughal, Zunairah; Talat, Haseeba; Muzaffar, Aliya (Annals of King Edward Medical University, 2024)
Background: Squamous cell carcinoma (SCC) in head and neck region has a high worldwide prevalence. Increased accuracy in diagnosis is achieved by immunohistochemical markers. Objectives: To evaluate the immunohistochemical expression of p63 and p40 in SCC and correlate with histological grades to determine p40 as a better potential diagnostic immunohistochemical marker for SCC. Methods: Descriptive cross-sectional study was conducted on eighty-three cases of SCC of head and neck from March 2020 to February,2022 at Pathology Department, KEMU, Lahore. Data including age, sex, risk factors and tumor site was collected. SCC grading was done on H&E stained tissue sections. Staining with p63 and p40 was performed and independently scored for percentage of tumor cells stained and intensity of nuclear staining. The results were compared using H-scores in all grades of SCC. Data was entered in Statistical Package for Social Sciences(SPSS-26). Quantitative variables like age were presented as mean ±SD. Qualitative variables as frequency and percentages. Correlation of two groups was done by applying Chi-square test. P value ≤0.05 was taken as significant. Results: SCC was graded according to the W.H.O. grading system. All cases stained positive for p63 and p40. Strong nuclear staining by p40 was observed in 65.02% cases versus 42.17% by p63. The mean tumor area stained by p40 was greater than p63 (90.35% vs 75.5%) in all cases. A significant higher mean H-score for p40 (9.69±2.86) versus p63 (7.05±3.12) was observed as indicated by significant P-value. The mean H-score of p40 immunoreactivity was 10.11 and p63 was 6.00 in poorly differentiated SCC. Males comprised 74.70% cases whereas females 25.30% only. SCC in oral cavity was (96.39%) followed by oropharynx and larynx. Conclusion: P40 immunohistochemical marker was better compared to P63 for the diagnosis of SCC particularly in poorly differentiated SCC.